Hepatoprotective Effect Of Daucus Carota Aqueous Root Extract Against Isoniazid And Rifampicin Induced Hepatotoxicity In Rats - B. BELLO,; A. M. WUDIL, (International Journal of Pharma and Bio Sciences, 2012)
The effects of pretreatment and co-administration of aqueous extract of Daucus carota root on anti-tubercular drugs hepatotoxicity in rats were studied. Wistar albino rats were divided into six groups of three rats each. Groups 1 and 2 were normal and test control (administered with anti-tubercular drugs to induce hepatotoxicity) respectively. Groups 3 and 4 were pretreated with 100mg/kg bw and 200mg/kg bw of the extract for 28 days, then administered with anti-tubercular drugs isoniazid (INH) and rifampicin (RMP) at doses of 27mg/kg bw and 54mg/kg bw respectively for same duration. In groups 5 and 6, same doses of the extract and anti-tubercular drugs were administered concurrently for 28 days. Oral administration of the extract significantly (P Ë‚ 0.05) reduced serum ALT, AST, and ALP activities, and uBIL concentrations compared to the test control. The results suggested that aqueous extract of Daucus carota might have had an hepatoprotective effect on anti-tubercular drugs hepatotoxicity in rats